ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MEKANISME KOPING PASIEN HEMODIALISA RSUD DR. M. YUNUS BENGKULU - Rustandi, Handi; Tranado, Hengky; Darnalia, Helen Xlara (Journal of Nursing and Public Health, 2018)
Chronic Renal Failure (CRF) disease is a clinical state of progressive kidney damage and variable from various causes of diseases. From the data in some of the nephrology center in Indonesia estimated the incidence and prevalence of chronic kidney disease each ranging from 100-150 / 1 million inhabitants and 200-250 / 1 million population, but were diagnosed with chronic renal failure on dialysis (Hemodialysis) only about 4000 to 5000 alone.This study aimed to determine the factors associated with the dominant coping mechanism on hemodialysis patients in hemodialysis unit of Dr. M. Yunus Hospital Bengkulu 2016.This study is an analytical research using cross-sectional design which use variable measurement or observation at a given moment. This study was conducted in Hemodialysis unit of Dr. M. Yunus Hospital Bengkulu on June 20 to July 20, 2016. The samples in this study were hemodialysis patients who had conducted dialysis over a year of 50 people. The instrument used were questionnaire and checklistsheets.Most respondents31 people from 50 respondents in hemodialysis unit of Dr. M. Yunus HospitalBengkulu adapted coping mechanisms. Almost all of the respondents21 people had little knowledge. Most respondents primary who had education level (primary and junior equivalents) were 21 of 50 respondents. Half of the respondents aged 41-60 were26 people from 50 respondents. The respondents totally 29 people were largely male. Most respondents that had high hopes were 25 respondents.